Clenbuterol and metformin ameliorate cachexia parameters, but only clenbuterol reduces tumor growth via lipid peroxidation in Walker 256 tumor-bearing rats - L.D.V. Henschel; M.E.R. de Lima; F.C. Fagundes; T. Horlem; M.F. Zazula; K. Naliwaiko; L.C. Fernandes (Brazilian Journal of Medical and Biological Research, 2025)
Cancer is the second leading cause of death worldwide. Cancer cachexia is a multifactorial catabolic syndrome responsible for almost one third of cancer-related deaths. Drug repurposing has been used in oncological research and drugs like clenbuterol and metformin seem to be reasonable candidates in the context of cancer cachexia, because the former is a β2-agonist that stimulates muscle gain and the latter has anti-inflammatory properties. The aim of this study was to assess the effects of a short-term treatment with metformin and clenbuterol, isolated or combined, on tumor growth and cancer cachexia parameters in Walker 256 tumor-bearing rats, a model of cancer cachexia. To this end, Wistar rats were separated into 8 groups and 4 of them were injected with Walker 256 tumor cells (W groups). Control (C) and W groups received the following treatments: metformin (M), clenbuterol (Cb), or metformin combined with clenbuterol (MCb). Body and tumor weight, metabolic parameters, and oxidative damage in the tumor were assessed. Compared to the C group, the W group showed body weight loss, hypoglycemia, hyperlactatemia, and hypertriacylglycerolemia. None of the treatments could reverse body weight loss, although they reversed the alterations of the assessed plasma metabolic parameters. Surprisingly, only clenbuterol alone reduced tumor weight. Hydrogen peroxide production and lipid peroxidation in tumor tissue was increased in this group. In conclusion, metformin and clenbuterol ameliorated metabolic cachexia parameters in Walker tumor-bearing rats, but only clenbuterol reduced the tumor weight, probably, through a lipid peroxidation-dependent cell death.